Eco-Profetik: Integrasi Pengetahuan Lokal dengan Islam tentang Lingkungan - Harifuddin Halim; Rasyidah Zainuddin; Fauziah Zainuddin (IAIN Ponorogo, 2017)
Abstract: The Segeri Society has a sacrosanct local knowledge system about animism, dynamism, and Sufism. It is manifested into the cosmological form that put nature and human beings as God's creatures that need each other. Therefore, Segeri people appreciate the natural environment. This research intends to reveal their local knowledge of the environment. The research was categorized into qualitative approach and it employed phenomenological research design. In collecting the data, the researcher utilized in-depth interview techniques and observations. Sources of data research were several informants namely: 'Bissu' that has authority over local belief and knowledge; 'Pananrang' that has authority of knowledge of astronomy; and 'Pallaoruma' who have the authority of knowledge about traditional farming. Local knowledge of Segeri people based on its relation to the natural environment (natural signs) and the non-natural environment (belief). Due to the emerge of Islamic Sufism, this knowledge is acculturated. Therefore, their environmental knowledge contains a sacred value called eco-prophetic. The existence of the value of sacredness in the local knowledge can be an inquiry for the modern science expert in returning the essence of science.الملخص: مجتمع سيجيري لديهم نظام المعرفة المحلية التوقيفية بين الوثنية والدينامية والصوفية. تتجلّى هذه المعرفة في شكل علم الكونيات الذي يضع الطبيعة والبشر كمخلوقات الله التي يحتاج بعضها إلى بعض. فبالتالي فإن مجتمع سيجري يقدرون بعمق البيئة الطبيعية. وبالتالى تهدف هذه المقالة إلى الكشف عن معارفهم البيئة المحلية. لذلك، يتم استخدام طريقة نوعية مع نهج الظواهر. استخدمت الدراسة لجمع البيانات تقنيات المقابلة المتعمقة والملاحظات. ومصادر البيانات البحثية هم المخبرون :